What is the Connection between Soil Carbon Dioxide Emission, Global Warming and Food Security? - Toro, Agnes; Harsányi, Endre (European Journal of Sustainable Development, 2019)
In the heart of the western civilization, mainly in the European Union, we are more interested in the quality of the food than in its quantity. Due to our ever-changing world we have to pay more attention to the future of the latter, namely to food security. As food security depends on global warming as well, one of its triggering actors was selected for analysis, the emission of carbon dioxide from the soil. The experiments were set up in the Látókép experimental site, which is situated in the eastern part of Hungary. I have examined the effect of less soil disturbance regarding the CO2 emission, in the case of winter ploughing, strip tillage and subsoiling methods. Measurements were performed with five differently placed and unique cylinders and with the help of the TESTO 535 measuring device. The results confirmed the hypothesis: less emission can help in the fight against global warming, thus it has a direct link to and impact on food security. Keywords: food security, global warming, CO2 emission, tillage methods